Design of a Single Phase HERIC-SPWM - Murdianto, Farid Dwi; Sudihato, Indhana; Karso, Anang Budi; Zulfa, Wildana (INTEK: Jurnal Penelitian, 2022)
Development in the field of technology has experienced rapid development in recent years, especially in inverter. Every year the development of inverters is very fast starting from full bidge inverters to HERIC inverters, inverters are usually used to convert DC voltage to AC, HERIC inverters are modifications of full bidge inverters with 2 additional IGBTs on the output side, therefore this paper will discuss about inverter design. HERIC SPWM 1 phase.The HERIC inverter will be compared with full bridge inverters to find out the advantages of these modifications. The modulation technique here uses SPWM (sinusoidal pulse width modulation) modulation technique as the switching process. IGBT switching on the HERIC inverter to produce the desired output waveform. The methodology for making a 1-phase HERIC SPWM inverter using a source from the PLN road network which will then be rectified by the rectifier. The rectifier output of 311 vdc will then be converted into AC voltage with output by the HERIC inverter.So that by making this single-phase HERIC SPWM inverter it is possible to be efficient and produce the power supply that will be used.